MicroRNA expression profiles in sinonasal biopsies to support diagnosis of granulomatosis with polyangiitis - Milanka Živanović; Alojzija Hočevar; Alojzija Hočevar; Nina Zidar; Metka Volavšek; Luka Bolha (Frontiers in Immunology)
ObjectivesTo identify aberrantly expressed microRNAs (miRNAs) in sinonasal tissue biopsies of patients with granulomatosis with polyangiitis (GPA), associate their expression profiles to sinonasal histopathology, and assess their differential expression between subgroups of clinically proven GPA patients, healthy controls and patients exhibiting inflammation of other etiology.MethodsWe included formalin-fixed, paraffin-embedded biopsy tissue samples of sinonasal mucosa from 37 patients with clinically proven GPA, 15 patients with inflammation of other etiology and 14 control patients with normal histology. Of the included GPA patients, 20 patients had characteristic GPA-related histological features, while 17 patients displayed non-specific GPA histopathology in their sinonasal biopsy. Assessment of histological parameters was performed using histopathological techniques, and analysis of miRNA expression with miRCURY LNA miRNA miRNome Human PCR Panels and quantitative real-time PCR.ResultsWe determined expression of 306 miRNAs in sinonasal biopsy samples, which displayed different extent of dysregulation between individual patient groups. Based on their potential to discriminate between the controls, non-GPA and GPA patient subgroups, dysregulation of 11 miRNAs was further assessed, of which miR-1-3p/-21-3p/-93-5p/-155-5p/-1248/-31-3p/-182-5p/-183-5p and let-7b-5p held the potential to stratify patients based on their sinonasal tissue miRNA profile. Notably, several of these miRNAs were associated with the presence of granulomas, vasculitis and necrosis in sinonasal biopsies of GPA patients.ConclusionOur study identifies novel miRNAs putatively implicated in the pathogenesis of GPA, and highlights dysregulated miRNAs as supporting biomarkers in establishing GPA diagnosis, particularly in the early phases of the disease, or in patients with atypical GPA presentation.